Liquidity Synchronization and Asset Valuation in Selected Emerging Asian Economies - Zaidi, Syeda Hina; Bhutta, Nousheen Tariq (Asian Economic and Financial Review, 2021)
This study examined the impact of liquidity synchronization on stock valuation in selected emerging economies in Asia. Empirical testing was motivated by the relevance of liquidity synchronization in asset pricing. Liquidity synchronicity is a non-diversifiable risk, which can affect the overall functioning of a market. The regulatory environments of Asian firms are different from those investigated in previous studies. Comprehensive analysis of the subject is limited in emerging economies mainly due to the small size of the markets and the constraint of data availability. A substantial knowledge gap provides the underlying foundation of this study. Three emerging economies of Asia – China, Pakistan and India – were selected for analysis using data from 2010 to 2019. The implied cost of equity pricing model and realized returns pricing model were employed to study the impact of liquidity synchronicity on asset valuation. Liquidity synchronization was found to have a significant impact on asset valuation in emerging Asian economies and the effect is stronger during market volatility.